Acinar adenocarcinoma of the lung in a cat: case report - J.O. Dhein; T.M. Veronezi; D.G. Gerardi; F.V.C. Amorim (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2023)
ABSTRACT Among the diseases that cause dyspnea in felines, primary pulmonary neoplasia is rare and tends to affect senile cats. This study reports the case of a seven teen year old FeLV infected cat who was diagnosed acinar adenocarcinoma of the lung and kidney metastasis. It presented prostration and anorexia and was hospitalized with dyspnea and pleural effusion. Chest radiography indicated increased radiopacity in the cranial portion of the right hemithorax, compatible with presence of intrathoracic mass and the cytologic analysis of pleural effusion suggested feline infectious peritonitis. The animal died two days after, and the definitive diagnosis was concluded after necropsy and histopathological examination. Pulmonary adenocarcinoma should be included with differential diagnosis of respiratory diseases in cats, especially the elderly.